Diagnostics of Fabry disease in arrhythmology practice: a case report - M. A. Dragunova; I. V. Kisteneva; E. N. Pavlyukova; L. P. Nazarenko; S. V. Popov (Российский кардиологический журнал)
Heart failure in Fabry disease (FD) is unfavorable prognostic manifestation and cause of death. Given that the disease is rare in clinical practice, the low awareness of physicians about this pathology leads to its late diagnosis and the lack of pathogenetic therapy.Aim. To present a clinical picture of the cardiovascular phenotype in FD in order to increase the awareness of doctors about this disease.Material and methods. In this clinical case, an asymptomatic FD course up to 46 years of age and mani festation in the form of arrhythmia were observed. According to echo car dio graphy, severe left ventricular hypertrophy (myocardial mass index, 214 g/m2) without signs of left ventricular (LV) outflow tract obstruction and left atrial (LA) dilatation were revealed (LA volume index — 47 ml/m2). Right ventricular (RV) and LV systolic function was assessed using two-dimensional speckletracking strain echocardiography. Latent subclinical RV and LV systolic dysfunction was established.Results.  Tandem mass spectrometry revealed a sharp decrease in alphagalactosidase activity of 0,03 umol/L/h (norm range, 0,80-15,00 umol/L/h), as well as an in creased Lyso-GB3 concentration of 95,18 ng/ml (normal range, 0,05-3,0 ng/ ml). A molecular genetic study of blood samples was carried out. By direct automatic sequencing of the GLA gene, a variant of the c.1229 C>T nucleotide sequence was identified, leading to the replacement of p.Thr4101le in the hemizygous state.Conclusion. This case shows the possibility and expediency of diagnosing FD in cardiology practice in patients with LV myocardial hypertrophy of unclear etiology, while atypical variants can be diagnosed only by molecular genetic testing.